The COVID-19 Intelligence Failure : why warning was not enough - Dahl, Erik J. (Washington, DC : Georgetown University Press, 2023)
"Erik J. Dahl examines the role of intelligence in providing advance warning to policymakers about the threat of pandemics. Dahl also considers the question of whether or not the Covid-19 pandemic was an intelligence failure. He begins the book by describing how both US national security intelligence agencies and public health surveillance organizations provide warning. He describes the similarities and differences between them and how these communities do and do not work together. Dahl goes on to argue that this pandemic was indeed a global intelligence failure, one in which the established worldwide system of collection and analysis was unsuccessful in giving sufficient warning to prevent the global spread of the disease. He explains why policymakers needed a different type of intelligence than what was available, and he makes recommendations for how the national security intelligence and public health communities can work more effectively together in the future. This pandemic could not have been completely avoided even with more actionable intelligence due to the nature of the disease and the Trump administration's aversion to accepting advice from the intelligence and scientific communities. However, unearthing intelligence in both secret and open sources to provide early warning of an outbreak is of paramount importance to giving policymakers the opportunity to avert or mitigate the effects of future pandemics"--
Are Pandemics a National Security Problem? -- What is the Role of the U.S. Intelligence Community? -- The Medical Intelligence, Surveillance, and Warning System -- Was the Coronavirus Pandemic an Intelligence Failure? -- Intelligence and Warning for the Future
Includes bibliographical references and index.
Keywords: COVID-19 (Disease); Public health surveillance; Pandemics; Intelligence service -- United States; Public health -- United States